Macroevolutionary Trade-Offs and Trends in Life History Traits of Cephalopods Through a Comparative Phylogenetic Approach - Ibáñez, Christian M.; Díaz-Santana-Iturrios, Mariana; Carrasco, Sergio A.; Fernández-Álvarez, Fernando A.; López-Córdova, David A.; Cornejo, Claudio F.; Ortiz, Nicolás; Rocha, Francisco; Vidal, Erica A. G.; Pardo-Gandarillas, María Cecilia (Frontiers in Marine Science, 2021)
One of the major mechanisms responsible for the animals’ fitness dynamics is fecundity. Fecundity as a trait does not evolve independently, and rather interacts with other traits such as body and egg size. Here, our aim was to correctly infer the macroevolutionary trade-offs between body length, egg length, and potential fecundity, using cephalopods as study model. The correlated evolution among those traits was inferred by comparative phylogenetic methods. Literature data on biological and reproductive traits (body length, egg length, and potential fecundity) was obtained for 90 cephalopod species, and comparative phylogenetic methods based on a previous molecular phylogeny were used to test the correlated evolution hypothesis. Additionally, we estimated the phylogenetic signal and fitted five different evolutionary models to each trait. All traits showed high phylogenetic signal, and the selected model suggested an evolutionary trend toward increasing body length, egg length, and fecundity in relation to the ancestral state. Evidence of correlated evolution between body length and fecundity was observed, although this relationship was not detected between body length and egg length. The robust inverse relationship between fecundity and egg length indicates that cephalopods evolved a directional selection that favored an increase of fecundity and a reduction of egg length in larger species, or an increase in egg length with the concomitant reduction of fecundity and body length in order to benefit offspring survival. The use of phylogenetic comparative methods allowed us to properly detect macroevolutionary trade-offs.